Exploring the trade-urbanization nexus in developing economies: Evidence and implications - Yuan Zhang; Guanghua Wan (Asian Development Bank Institute (ADBI), 2017)
Developing countries have seen a rapid rise in population urbanization in the past decades. At the same time, they have participated actively in the process of globalization. However, possible interlinks between population urbanization and trade openness in developing economies have been ignored by present literature. This paper firstly proposes a simple framework explaining the cereals trade-population urbanization nexus, showing how cereals supply constrains population urbanization and how international trade can change this constraint. Then, it presents historical evidence, empirical tests, and case studies from the People's Republic of China and India further highlighting the critical role of cereals trade in population urbanization in developing economies. Policy suggestions that may help developing countries achieve more inclusive and sustainable urban development are discussed in the final section of this paper.
Keywords: Q17; O18; R11; 330; trade; urbanization; trade-urbanization nexus; trade openness; cereals trade; population; developing economies; urban development